Evaluating the Economic Efficiency of Agricultural Producing Cooperatives A Case Study of Sirjan City - A Karbasi; N Ohadi (تعاون و کشاورزی, 2011)
The main objective of this study was to determine the economic efficiency and factors affecting it by using stochastic frontier function for Sirjan agricultural producing cooperatives in 2010. Collected data were analyzed using Frontier 4.1 software. The results of this study show that average economic efficiency of Sirjan agricultural producing cooperatives was 73%. The result also indicates that current capital value of company has a direct & significant relationship with frontier profit and there is a reserve relation between numbers of activities of the company with frontier profit. In the evaluation of economic inefficiency of agricultural producing cooperative, managing director''s experiences and duration of cooperative company have a positive influence upon economic efficiency but costs related to all of activities of the cooperative companies and diversity of activities have a negative influence upon economic efficiency. This study suggests the reduction of company’s activities and increased investments in agricultural producing cooperatives, which can increase the profitability of these companies. Also, utilizing managers with high experiences, application of correct management & offering the much needed training and extension activities can promote economic efficiency of these companies